Aromatic Amino Acid Mutagenesis at the Substrate Binding Pocket of Yarrowia lipolytica Lipase Lip2 Affects Its Activity and Thermostability. (13th August 2014) - Wang, Guilong; Liu, Zimin; Xu, Li; Yan, Yunjun
Abstract : The lipase2 from Yarrowia lipolytica (YLLip2) is a yeast lipase exhibiting high homologous to filamentous fungal lipase family. Though its crystal structure has been resolved, its structure-function relationship has rarely been reported. By contrast, there are two amino acid residues (V94 and I100) with significant difference in the substrate binding pocket of YLLip2; they were subjected to site-directed mutagenesis (SDM) to introduce aromatic amino acid mutations. Two mutants (V94W and I100F) were created. The enzymatic properties of the mutant lipases were detected and compared with the wild-type. The activities of mutant enzymes dropped to some extent towards p -nitrophenyl palmitate ( p NPC16) and their optimum temperature was 35°C, which was 5°C lower than that of the wild-type. However, the thermostability of I100F increased 22.44% after incubation for 1 h at 40°C and its optimum substrate shifted from p -nitrophenyl laurate ( p NPC12) to p -nitrophenyl caprate ( p NPC10). The above results demonstrated that the two substituted amino acid residuals have close relationship with such enzymatic properties as thermostability and substrate selectivity.